2019
DOI: 10.31234/osf.io/smdyp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imagining a Sustainable World: Measuring Cognitive Alternatives to the Environmental Status Quo

Abstract: We build on social identity models of environmental collective action by considering the role ofpeople’s access to cognitive alternatives to the environmental status quo. We developed a new measure of cognitive alternatives to the environmental status quo, and examined its ability to predict environmental activist identification and willingness to engage in environmental activism. In Study 1 (N = 386), we developed the initial scale, and found evidence for its reliability and validity. The ability to imagine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 4 publications
2
12
0
Order By: Relevance
“…How can these collective acts in support of climate action be explained, and how can further collective action in support of proenvironmental initiatives be promoted? Drawing on Social Identity Theory (SIT), Wright, Schmitt, Mackay, & Neufeld (2020) proposed that engagement in environmental collective action would be more likely for people who can clearly imagine what a sustainable world would be like. In two studies, they demonstrated that being able to imagine what a sustainable world would be like is associated with self-reported pro-environmental behavior and self-reported willingness to engage in pro-environmental collective action in the future.…”
Section: Access To Environmental Cognitive Alternatives Predicts Pro-environmental Activist Behaviormentioning
confidence: 99%
See 4 more Smart Citations
“…How can these collective acts in support of climate action be explained, and how can further collective action in support of proenvironmental initiatives be promoted? Drawing on Social Identity Theory (SIT), Wright, Schmitt, Mackay, & Neufeld (2020) proposed that engagement in environmental collective action would be more likely for people who can clearly imagine what a sustainable world would be like. In two studies, they demonstrated that being able to imagine what a sustainable world would be like is associated with self-reported pro-environmental behavior and self-reported willingness to engage in pro-environmental collective action in the future.…”
Section: Access To Environmental Cognitive Alternatives Predicts Pro-environmental Activist Behaviormentioning
confidence: 99%
“…Additionally, there is evidence that politicized identities-identification with activist groups-is a stronger and more proximal predictor of collective action than identification with broader categories (Schmitt, Mackay, Droogendyk, & Payne, 2019;Simon & Klandermans, 2001;Simon et al, 1998). For example, Schmitt et al (2019) and Wright et al (2020) found stronger correlations between politicized environmental identification and pro-environmental activist behaviors than between identification with nature and pro-environmental activist behaviors.…”
Section: Social Identity Theory and Environmental Actionmentioning
confidence: 99%
See 3 more Smart Citations